Salinity induced alterations in ionic concentration of haemolymph and its effects on histopathology of gills and digestive gland in razor clam (Solen dactylus von Cosel, 1989; Bivalvia, Solenidae) - Farzadfar, Fariba; Doustshenas, Babak; Rezaie, Annahita; Mousavi, Seyed Mohammad (Molluscan research, 2021)
Solen dactylus is one of the most common razor clams in the tidal zone in the western Indian Ocean and Persian Gulf. Habitats of these clams may be subject to salinity fluctuations due to high evaporation and heavy rainfall. To assess their adaptation, in the laboratory clams were placed in 50-litre tanks with 40 cm depth of natural substrate and were kept in salinity of 45 ppt for a week before subsequent experiments. They were then exposed to salinities of 5, 20, 35, 45 and 65 ppt for three weeks. Concentrations of Na + , Cl - , K + , Ca 2+ , and Mg 2+ , as well as osmolality in the haemolymph and tank water were measured at 1, 24, 72 h, one week and three weeks after the start of the experiment. Haemolymph Na + and Cl - values followed the concentrations of the external medium so that they decreased at low salinities and increased at high salinities. The Ca 2+ , Mg 2+ and K + ions all showed a common pattern, and their trend was independent of the external environment. Histopathological analysis showed severe tissue damage at low salinities with expanded intercellular spaces, an increase of intracytoplasmic vacuoles in the digestive tubules, and necrosis and destruction of lamellae in gill tissues.